Evaluation of the Ground Water in Baghdad Governorate / Iraq - Hassan Al–Basrawi, Naseer; H. Awad, Jamal; A. Hussain, Tariq (Iraqi Journal of Science, 2023)
The coverage area of Baghdad Governorate area is considered as a part of theMesopotamia plain, which belongs to the unstable shelf. This area is totally coveredby quaternary sediments. The sediments are composed mainly by cyclic alteration ofclay, silt, sand and very fine gravels. Quaternary sediments represent the mainaquifer for all parts of Baghdad governorate.Arc GIS 9.3 and GMS 6.5 programs were used in drawing high accurateestimating maps, to define salinity, type of the ground waters, the general directionof their movement, the distribution values of transmissivity of upper aquifer, withdistribution and the amount of draw down for these wells, also drawing map for theground waters depth zones.It can be concluded that the salinity of the ground water in Baghdad Governorateranges between (fresh water – Brine water) in general, with the predominance ofchloridic water type and the presence of sulphatic water type in other places. Thedirection of the ground water movement is mainly from the west towards the eastand north and southeast, with the presence of local movements other directions. Thetransmissivity coefficient ranges between (50 – 350) m2 / day in general, but thesevalues decrease toward the east, especially east of the Tigris River as indicated bythe level of draw down in the wells, which ranges between (2 – 10) m. The resultsreflect that the ground water depth in Baghdad Governorate ranges between (2 – 50)m depending on the distance from the river and irrigation channels, which areconsidered as sources of water recharge to the ground water.